Conflicting Agendas In Care For Olympic Amateur Boxing - Diep, Dion (The Meducator, 2018)
Boxers face a wide variety of health risks: strenuous movements, harsh training regimens, rapid dehydration, and repeated blows to the head and body. In this global perspective, I elaborate on my role in the boxing community as part of the medical team, reflect on the barriers to care, and present future directions.